Analisis Tingkat Kecemasan Matematika Mahasiswa Pada Mata Kuliah Geometri Analitik - Nurfadilah .; Hasanuddin . (CV.ITTC INDONESIA, 2026)
Mathematics is a branch of science that plays a crucial role at every level of education. However, its inherently abstract nature often triggers mathematics anxiety among students. This study aims to describe the level of learning anxiety among students in the Analytical Geometry course. The study employed a quantitative descriptive approach involving 28 students selected through purposive sampling. Data collection was conducted using a questionnaire containing four anxiety indicators: mathematical knowledge/understanding, somatic, cognitive, and attitude. Data analysis revealed that students’ levels of learning anxiety fell into the high category, with an average score of 55.39. More specifically, 88% of the students fell into the high to very high anxiety category. These findings indicate that learning anxiety remains a significant barrier in the learning process, particularly in mastering Analytical Geometry material. Therefore, innovative learning strategies and the creation of a conducive learning environment are needed to help reduce students’ anxiety levels.